The Analytic/Continental Divide of Contemporary Philosophy - A Hesamifar (Metaphysics, 2013)
At the beginning of the twentieth century, when other philosophical tendencies were in the ascendance, two important movements emerged which rapidly came to dominate the intellectual domain: analytic philosophy and continental philosophy. The prominence of these two traditions caused the most famous classification of contemporary philosophy into analytic/continental. But this division created problems such as: Is it a comprehensive and exclusive division and could it cover all trends of contemporary philosophy? What are the features of each school which distinguish it from the other? This article tries to explain the relation between analytic philosophy and continental philosophy, and to evaluate the efforts which have been done to justify the division.